Mapping ASEAN : achieving peace, prosperity, and sustainability in Southeast Asia - Carden, David L. (Indiana University Press, 2019)
"For half a century, ten dynamic nations in Southeast Asia have been implementing a shared vision of economic growth, sustainable development, and cultural progress. Today, the economies of those nations are linked inextricably with the future of greater Asia as well as with the United States and the other Western countries. With authoritarianism and protectionism on the rise around the world and the catastrophic effects of global warming making action urgent, the nations that form the Association of Southeast Asia Nations are more relevant and under greater political and social stress than ever. In these illuminating pages, David Carden, the first American resident ambassador to ASEAN, paints a vivid portrait of the regional and global cooperation required to meet today, and interconnected future. Carden takes us behind the scenes as the leaders of these ten nations work to prepare their countries and their region for the 21st century. Carden persuasively argues that the unfolding story of the ASEAN nations is a story for the entire world that we are all increasingly interdependent and confronted with the existential need to solve the same set of challenges"--